VALUE OF SPECIFIC PARAMETERS AND INTEGRATIVE INDICES OF TREADMILL TEST FOR THE ASSESSMENT OF CORONARY STENOSIS SEVERITY - S. Yu. Martsevich; S. N. Tolpygina; A. M. Malysheva; Yu. N. Polyanskaya; E. A. Gofman; O. V. Lerman; V. P. Mazaev; A. D. Deev (Кардиоваскулярная терапия и профилактика)
Aim. To assess the value of specific parameters and integrated indices (II; such as Duke Index (DI), Centre for Preventive Medicine Index (CPMI), and modified CPMI) of the treadmill test in the diagnostics of coronary stenosis severity among patients with stable coronary heart disease (CHD).Material and methods. The study included all patients (260 permanent residents of Moscow City or Moscow Region) who were admitted to the State Research Centre for Preventive Medicine with the CHD diagnosis and who underwent coronary angiography (CAG) and treadmill test in the period between January 1st 2004 and December 31st 2007.Results. There were statistically significant associations between the main treadmill test parameters and the severity of coronary artery (CA) atherosclerosis. The larger number of stenosis-affected CA was associated with a higher prevalence of chest pain and treadmill tests with positive results and ST segment depression >1 mm, as well as with a decreased total duration of treadmill test. Similarly, the increased risk, as assessed by treadmill test indices (DI, CPMI, and modified CPMI), was linked to an increased number of stenosis-affected CA. Modified CPMI demonstrated the highest diagnostic value for the assessment of coronary atherosclerosis severity.Conclusion. The treadmill test parameters which demonstrated their diagnostic value for the assessment of CHD severity included the following: positive test results, retrosternal chest pain as the reason for test discontinuation, ST segment depression >1mm, and short total duration of the test. Overall, all II demonstrated their high value in CHD diagnostics. Modified CPMI was the most effective II in the assessment of CA atherosclerosis severity.